Pengaruh Media Flashcard dalam Pembelajaran Bahasa Arab Melalui Mufrodad pada Peserta Didik SMA Nurul Jadid Kelas X - Siti Nor Halimah; Munirul Abidin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of using flashcard media in Arabic language learning, specifically in mastering mufrodat (vocabulary), among tenth-grade students at SMA Nurul Jadid. The research employed a quantitative approach with a quasi-experimental design involving two classes as the experimental and control groups. The instruments used were pretest and posttest assessments. Data analysis results showed a significant increase in posttest scores in the experimental group compared to the control group. The average posttest score of the experimental group reached 83.4, while the control group only achieved 70.5. A t-test indicated a statistically significant difference, suggesting that flashcard media is effective in improving students’ vocabulary skills. These findings suggest that the use of interactive visual media such as flashcards can enhance student engagement and understanding in Arabic learning. This study also implies that teachers should consider using media suited to student characteristics and learning materials. However, the limited scope of participants and time of implementation are important considerations for future research. The researcher recommends developing digital media and conducting further studies at different educational levels or contexts.